2017
DOI: 10.1111/cyt.12451
|View full text |Cite
|
Sign up to set email alerts
|

Referral population studies underestimate differences between human papillomavirus assays in primary cervical screening

Abstract: Objective: We studied how representative cytologically abnormal women ("referral populations") are with respect to uncovering differences between human papillomavirus (HPV) assays in the primary screening where most women are cytologically normal.Methods: A total of 4997 women were tested with SurePathâ cytology, and Hybrid Capture 2 (HC2), cobas, CLART and APTIMA HPV assays. Women with positive test results were offered a follow-up. For all detected HPV infections and HPV-positive high-grade cervical intraepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Although we have repeatedly shown that inter-assay concordance is indeed less of a problem in women who would benefit from treatment of histologically confirmed lesions (cervical intraepithelial neoplasia of stage 2 or more; CIN2) [6e8], we also reported that assays show more discordant findings when these lesions are cytologically normal [8]. In plain terms, this occasional lack of concordance is the difference between detecting or missing a lesion that should be treated.…”
Section: Dear Sirmentioning
confidence: 73%
“…Although we have repeatedly shown that inter-assay concordance is indeed less of a problem in women who would benefit from treatment of histologically confirmed lesions (cervical intraepithelial neoplasia of stage 2 or more; CIN2) [6e8], we also reported that assays show more discordant findings when these lesions are cytologically normal [8]. In plain terms, this occasional lack of concordance is the difference between detecting or missing a lesion that should be treated.…”
Section: Dear Sirmentioning
confidence: 73%
“…Moreover, cotesting is also being performed in a pilot population-based program that is still ongoing in Malta [115]. Other countries, such as Denmark, which performs HPV testing for women in the age range of 60–64 [169,170] and Belgium [138], are still evaluating HPV primary screening for implementation in their national programs.…”
Section: The Current Landscape Of Cervical Cancer Screening In Thementioning
confidence: 99%
“… 13 The Patobank can be considered satisfactorily complete for cervical cytology since 2005 and for cervical histology since 2009. 14 Colposcopies are not registered in the Patobank. Because the national guidelines recommended taking blind biopsies if no lesion could be visualized colposcopically, a record of a biopsy was used as an indicator that a colposcopy took place.…”
Section: Methodsmentioning
confidence: 99%